Inclusão escolar de alunos com deficiência : interface com os conteúdos da Educação Física - Carvalho, Camila Lopes de (Educación Física y Ciencia.)
Physical Education has been redefined in recent decades, its objectives, aims, contents and performances at school, at the same time, that it has incorporated ideas of inclusion socially established. Thus, the aim of this study is to analyze the process of inclusion of students with disabilities in Physical Education in their main content. Therefore, a qualitative survey was conducted, consisting of a case study, where lessons of physical education in a class of 2nd year of elementary school, which has two students with disabilities, were observed for 1 school year, with data analysis by categorization. A predominance of positive aspects to the inclusion was seen (active participation and positive interactions among all the classes), but intermingled with other negative (Game and Sports over others contents, and negative interactions in competitive and technical activities). In conclusion, there is a positive construction of inclusive physical education at schools but there is a need for more professional training to explore the different contents of Physical Education and associate them to inclusive education.